(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Handcrafted fabrics such as atlas, adras, and beqasam hold a significant place in Uzbekistan’s cultural heritage and traditional craftsmanship. These fabrics, known for their vibrant colors, intricate patterns, and high-quality weaving techniques, have been used for centuries in clothing, home décor, and ceremonial garments. Atlas, a luxurious silk fabric with soft textures and bold colors, is commonly used for festive and bridal wear. Adras, a blend of silk and cotton, is more durable and versatile, making it suitable for both fashion and interior design. Beqasam, a heavier fabric with complex geometric designs, is traditionally used for outerwear and upholstery. In contemporary fashion and design, these fabrics continue to inspire designers who integrate them into modern apparel, accessories, and interior decoration. The revival of handcrafted textiles aligns with the global sustainable fashion movement, promoting eco-friendly production methods and ethical craftsmanship. Additionally, their unique ikat weaving technique makes them highly valuable in the international fashion market. This paper explores the historical significance, artistic characteristics, and evolving role of atlas, adras, and beqasam in modern design while highlighting their importance in preserving cultural identity and sustainable fashion.